Pengaruh Pendekatan Scaffolding dalam Pembelajaran Matematika terhadap Prestasi Belajar Siswa di MTsN Jambewangi Selopura Blitar - Moh. Nasrul Fuad; Muhammad Zainuddin MZ; Nizar Zakaria (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
This study aims to test the effect of the scaffolding approach in mathematics learning on student achievement at MTsN Jambewangi Selopuro Blitar. With a quantitative approach and quasi-experimental research type, this study used a randomized post-test group design. Class VIII G as the control class and VIII H as the experimental class, with 37 students each, were selected using cluster sampling techniques. Data were collected through tests and analyzed with the Independent Samples T Test. The results showed that the scaffolding approach had a significant effect on student achievement, so it can be an alternative effective learning method to improve students' ability to understand mathematical concepts. The scaffolding approach is a very effective learning method in improving student achievement, especially in understanding complex mathematical concepts. By providing appropriate assistance and support in the early stages of learning, students can build a strong foundation and improve their abilities gradually. Therefore, the scaffolding approach can be an alternative effective learning method for teachers to improve student learning outcomes.